Trends and recurrence of stillbirths in NSW - Jillian A. Patterson; Jane B. Ford; Jonathan M. Morris; Christine L. Roberts (Elsevier, 2014)
Abstract Objective: To examine the trend in stillbirth rates adjusted for the trends in the maternal risk profile, and to use local data to estimate the stillbirth recurrence risk. Methods: Linked hospital, birth and perinatal death review data were used to identify risk factors and stillbirths among women giving birth to singletons in NSW between 2001 and 2009. Logistic regression models were developed to predict stillbirth rates based on the changes in the maternal population. Results: Between 2001 and 2009 there were 3,449 stillbirths (4.4 per 1,000 births), with no significant change in rate overall (p=0.6) or across older gestational age categories (26-33 weeks p=0.67, ≥34 weeks p=0.36), and a slight increase at <26 weeks (p=0.01). However, when changes in the maternal population were taken into account, there was a significant increase in stillbirths at <26 weeks (p<0.001). Women with a stillbirth in a first pregnancy were at increased risk of stillbirth in their second pregnancy (4.3 95%CI 2.4-7.7). Conclusion: There has been no decline in the stillbirth rate in NSW in recent years, which, at late gestations, may be accounted for by changes in the maternal population. At early gestations, there has been an increase in stillbirths where a decrease in rate may be expected based on the maternal population. Implications: Further focus on addressing risk factors for stillbirths is needed to ensure continued progress is made in reducing stillbirths.